2015
DOI: 10.1016/j.coal.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of geological modeling processes on spatial coalbed methane resource estimation

Abstract: Spatial coalbed methane (CBM) resources estimation is based on spatial distributions of coal, coal adsorbed gas content and coal density. However, the spatial distribution of gas content can be generated via two different geological modeling processes: (1) The gas content distribution is generated by geological modeling based on the interpreted gas content at boreholes; (2) Distributions of gas content related logs or coal properties are generated firstly, then the gas content distribution is calculated based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The package of petrel reservoir engineering core modules, combined with an ECLIPSE industry-reference simulator, provides a set of numerical solutions for forecasting the dynamic reservoir processes and for designing plans for the exploration, development, and production. The modeling of bituminous coal seams using Schlumberger Petrel software enables to perform numerical simulations of coal bed methane extraction by means of directional drilling from the surface [19,20], as well as computer simulations of enhanced methane recovery combined with injecting CO 2 into the coal seams-enhanced coal bed methane (ECBM) [24][25][26][27][28][29][30][31].…”
Section: Institution Cbm Resources (Million Nm 3 )mentioning
confidence: 99%
“…The package of petrel reservoir engineering core modules, combined with an ECLIPSE industry-reference simulator, provides a set of numerical solutions for forecasting the dynamic reservoir processes and for designing plans for the exploration, development, and production. The modeling of bituminous coal seams using Schlumberger Petrel software enables to perform numerical simulations of coal bed methane extraction by means of directional drilling from the surface [19,20], as well as computer simulations of enhanced methane recovery combined with injecting CO 2 into the coal seams-enhanced coal bed methane (ECBM) [24][25][26][27][28][29][30][31].…”
Section: Institution Cbm Resources (Million Nm 3 )mentioning
confidence: 99%
“…Numerous researchers have reported the use of Monte Carlo simulations for modeling methane gas emission, with the results compared to those of stochastic modeling to re ect the acceptability of the simulation results (Zhou, 2015). In these studies, gas methane emission prediction has been based on the data on the coal structure, coal thickness, coal quality, and gas content (Zhou, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al built regression equations for gas content vs depth and gas content vs depth plus ash, and they found that the latter had a high correlation coefficient, which they then used to calculate the gas content . Based on the relationship of the measured gas content and the logs of gamma-ray, density, and depth, Zhou et al created an artificial neural network model to simulate the spatial distribution of the gas content . Zhou and Guan calculated the gas content from a regression equation using ash, volatile matter content, fixed carbon content, and depth as parameters .…”
Section: Introductionmentioning
confidence: 99%